2019
DOI: 10.2355/isijinternational.isijint-2018-710
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Behavior of Blast Furnace Tuyere

Abstract: This study focuses on the study of erosion pattern of Blast furnace tuyere which is a copper casted component used for injecting hot air inside the furnace to help in combustion of pulverized coal. As tuyere is operating at high adverse thermal condition; it has provision of two cooling circuits, body and nose separated by solid copper. Identification of the most vulnerable zone in tuyere has been done by scanning used tuyere for which nose cooling circuit does not get failed. This is required to get the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A previous study by Rajeswar et al had compared the used tuyere (not failed) with the original tuyere to identify the vulnerable zones. [ 8 ] It was reported that the top part of nose zone of tuyere exhibits the maximum material loss. The hotspot is observed at similar zones in these designs reinforcing the vulnerability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Rajeswar et al had compared the used tuyere (not failed) with the original tuyere to identify the vulnerable zones. [ 8 ] It was reported that the top part of nose zone of tuyere exhibits the maximum material loss. The hotspot is observed at similar zones in these designs reinforcing the vulnerability.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al have explained three categories of tuyere failure, erosion and melting, bending, and crack propagation. [ 6 ] Out of these, the mechanism of erosion and the subsequent failure have been elaborated by Gao et al [ 7 ] The erosion pattern of the tuyere has also been exposed by comparing the used tuyeres with the original model by Chatterjee et al [ 8 ] It was found that the top part of the tuyere nose is the most vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the erosion types of the tuyeres are very complex and can be classified into four categories: melting erosion, point erosion, cracking, and deformation of the tuyere. Chatterjee et al [ 8 ] found that there is a significant amount of material loss at the front end of the tuyere compared to other parts of the tuyere. To reduce erosion at the top of the tuyere, better wear‐resistant materials should be sprayed in this area to enhance the life of the tuyere.…”
Section: Introductionmentioning
confidence: 99%
“…A simulation study of water circuit in the cooling system demonstrated that the highest temperature was on the top part of the tuyere tip, i.e., the vulnerable zone of the tuyere, which was consistent with the worn tuyere in the production line. [ 6 ] The limescale has been found as a key factor affecting the temperature in the cooling system. [ 7,8 ] The encrustation of limescale reduced the heat conduction, increased the temperature of the tuyere, and resulted in melting loss.…”
Section: Introductionmentioning
confidence: 99%